An Introduction to Infophilia, A Positive Psychology of Information - Coleman, Anita S. (Journal of Information and Knowledge, 2025)
The goal of Brenda Dervin’s groundbreaking research was not just to develop the sense-making theory but also to “invent communication alternatives and assess their utility.” One of her practice inventions was the ‘Good News newsletter,’ where she created info-sheets for schools and clinics (Neill, 1992, p. 6). Like Dervin, I’ve sought to create new forms of communication through my work as a library school faculty, grounded in prosocial theorizing and contributing to my profound satisfaction. Appendices 1 – 4 detail a case study of my research to showcase prosocial theorizing but this is a background story. In this paper, I focus on my recent research which began last September. I started a weekly Substack newsletter Infophilia, a positive psychology of information to write about it (2023). The newsletter is one of the primary places where I’m drawing from many disciplines, cultures, languages, and societies, to develop and discuss the infophilia theory and framework, an evolutionary, socio-cultural, positive psychology of information. Three infophiles, lovers of information— my father, my husband, and my doctoral advisor, Linda Smith — first made me aware of the human affinity for information with their distinctive information styles. William James’ “lived hypothesis” encourages researchers to experiment with life’s practical challenges and my infophilia work emerges from just such a spirit of curiosity, observation, and experimentation. First, I offer a personal poem in Tamil. Then, I describe the roots of infophilia in positive psychology and infophilic information styles and how it can be measured in individuals. Then, I close with a ‘truth’ story, some metaphors, and the bold ideas that a theory of infophilia offers for global library and information studies and research, however defined.